Planear las comidas: Use una lista de compras - Claudia Peñuela (EDIS, 2011)
Have you ever gotten home from the grocery store and realized you forgot to buy what you went for? Have you bought foods that you already have at home? Keep this from happening to you again. Write your shopping list before going to the store — it saves time and money. This 2-page Spanish-language fact sheet was written by Claudia Peñuela and published by the UF Department of Family Youth and Community Sciences, May 2011.